(untitled) (Research, Society and Development, 2022)
Introduction: For speech to exist, there must be motor control of phono articulatory organs involved. Speech motor control, which sends information in order to contract muscles and structures such as lips, tongue and jaw and recruits them to perform precise and coordinated movements, includes planning, which would be the preparation of movements and programming of the speech. preparation and production of these sounds. Objective: To understand the role of Brazilian speech therapists in children’s speech motor disorders. Method: A questionnaire was developed to investigate the clinical practice of speech therapy and knowledge about Motor Speech Disorders (MPD), where 95 speech therapists completed an online questionnaire, developed exclusively for this research. The questionnaire was developed using the Google Forms TM platform; with closed questions. The study is characterized by being exploratory, cross-sectional, descriptive, quantitative. For data analysis, after completion, the subjects’ data were tabulated individually and thus underwent statistical treatment and quantitative description. Results: This study favored the characterization of who are the professionals who work with FMD in Brazil and showed that most are from the private health network and had some training dedicated to the performance of these disorders. The data are also explained in relation to the dynamics of care, frequency and duration, demonstrating that the service in Brazil is far from international realities.